2006
DOI: 10.1158/1078-0432.ccr-06-1405
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinases: New Targets for Cancer Therapy

Abstract: The Aurora kinase family is a collection of highly related serine/threonine kinases that functions as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
199
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 47 publications
2
199
0
4
Order By: Relevance
“…Human Aurora-A is commonly amplified in epithelial malignant tumors, and more than 50% of ovarian and breast cancers show enhanced activation of this kinase (13,14). It has been shown that rodent fibroblasts transfected with Aurora-A form tumors in nude mice, indicating that Aurora-A is a cancer susceptibility gene (15).…”
Section: Introductionmentioning
confidence: 99%
“…Human Aurora-A is commonly amplified in epithelial malignant tumors, and more than 50% of ovarian and breast cancers show enhanced activation of this kinase (13,14). It has been shown that rodent fibroblasts transfected with Aurora-A form tumors in nude mice, indicating that Aurora-A is a cancer susceptibility gene (15).…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent evidence suggests a group of serine-threonine kinases, known as Aurora kinases, to have an important role in carcinogenesis as key regulators of mammalian mitosis, crucial for identical and exact segregation of genomic material during cell division. 3 It is proposed that aberrations of chromosome segregation potentially causes aneuploidy and is therefore triggering carcinogenesis. 4 Thus, it is not unexpected that these kinases have been described to be related with chromosomal instability, agressive growth and poor outcome in leukemia and in various malignancies like breast, bladder, ovarian, pancreatic and colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 AURKB is found on chromosome 17p13, an area not typically amplified by tumors. 3 Beside the lack of amplification on gene level, several studies revealed an overexpression of mRNA and protein levels in several malignancies, associated with lymph node invasion, proliferation and metastasis. [14][15][16][17][18] AURKB belongs to the family of chromosomal passenger proteins and is essential for accurate chromosomal segregation and orientation, spindle assembly checkpoint, chromosome condensation, nuclear envelope formation and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AURKA is highly expressed relative to normal tissue and amplified in multiple human tumors (Zhou et al, 1998). Amplification of the AURKA gene has been taken as evidence that the kinase activity of AURKA is under selective pressure during tumorigenesis, and, as a consequence, inhibitors of AURKA kinase are being developed as anticancer therapeutics (Carvajal et al, 2006). In addition to neuroblastoma both MYCN and AURKA are expressed at high levels in glioblastoma, astrocytoma, and prostate carcinoma, suggesting that stabilization of MYCN by AURKA may not be restricted to childhood tumors.…”
Section: Discussionmentioning
confidence: 99%